2017
DOI: 10.1002/ana.24846
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine therapy‐mediated neuroprotection in a Friedreich's ataxia mouse model

Abstract: ObjectivesFriedreich's ataxia is a devastating neurological disease currently lacking any proven treatment. We studied the neuroprotective effects of the cytokines, granulocyte‐colony stimulating factor (G‐CSF) and stem cell factor (SCF) in a humanized murine model of Friedreich's ataxia.MethodsMice received monthly subcutaneous infusions of cytokines while also being assessed at monthly time points using an extensive range of behavioral motor performance tests. After 6 months of treatment, neurophysiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 56 publications
3
28
0
1
Order By: Relevance
“…We recently demonstrated that the BM stem cell–mobilizing cytokines G‐CSF and SCF display strong neuroprotective effects in the YG8R mouse model (without prior BMT) 16. Here, we show that the combination of G‐CSF and SCF not only displays direct neuroprotective effects in FA,16 but also aids the delivery of BM cells to sites of FA‐associated injury, stimulating neural repair.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…We recently demonstrated that the BM stem cell–mobilizing cytokines G‐CSF and SCF display strong neuroprotective effects in the YG8R mouse model (without prior BMT) 16. Here, we show that the combination of G‐CSF and SCF not only displays direct neuroprotective effects in FA,16 but also aids the delivery of BM cells to sites of FA‐associated injury, stimulating neural repair.…”
Section: Discussionmentioning
confidence: 59%
“…These mice are frataxin‐deficient and develop progressive neurodegeneration and cardiac pathology 16, 21, 30…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations